Discovery and re-use of scholarly literature:Citing, reference management and collaboration tools - Kabale University (Kabale University, 2023)
Understand the concept of citing a copyrighted work in relation to plagiarism, become familiar with commonly used citation styles, know why, when and how to cite. Use citation styles in office operation in Microsoft word and Google documents and become familiar with reference management tools. Use web versions of Mendeley/Zotero as an example of such tools. and collaborate with their peers by using such tools.